Crimes and humor in Domingo Villar’s novels - Rivero Grandoso, Javier (Madrygal. Revista de Estudios Gallegos, 2011)
In this article we try to stress the importance of humor in the work of Domingo Villar. Our objective is to analyze the comic situations that the author creates in order to discover the humoristic elements used and the purpose of them. It is essential for us to study the configuration of the characters and the reoccurring use of stereotypes to discover the role of humor in Ollos de auga and A praia dos afogados, two novels highly appreciated by the public and critics.